2018
DOI: 10.1177/1757177418765634
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Middle East respiratory syndrome coronavirus among febrile Indonesian Hajj pilgrims: A study on 28,197 returning pilgrims

Abstract: There were 211,000 Indonesian Hajj pilgrims going to Mecca through 11 main airports in 2015 who were at risk of contracting the Middle East respiratory syndrome coronavirus (MERS-CoV). We aimed to find out whether there was any occurrence of MERS-CoV by performing screening on 28,197 returning pilgrims. Those with a body temperature of > 38 °C and respiratory symptoms were sent to the airport clinic to have an oropharyngeal swab and a bacterial culture. Fifteen pilgrims had fever (> 38 °C) accompanied by respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 15 publications
3
16
0
Order By: Relevance
“…One observational study 21 and two mathematical modelling studies 19,23 were conducted in the context of the Covid-19 pandemic; the remaining studies were conducted during the influenza A pandemic (H1N1) 2009 [14][15][16]18,20,22,24 17 pandemics. Three studies were conducted in Japan, 16,18,24 two in Taiwan 15,21 and one each in Australia, 20 China, 14 Indonesia, 17 Singapore, the UK 23 and the USA. 19 Where reported, the study population comprised adults and children.…”
Section: Resultsmentioning
confidence: 99%
“…One observational study 21 and two mathematical modelling studies 19,23 were conducted in the context of the Covid-19 pandemic; the remaining studies were conducted during the influenza A pandemic (H1N1) 2009 [14][15][16]18,20,22,24 17 pandemics. Three studies were conducted in Japan, 16,18,24 two in Taiwan 15,21 and one each in Australia, 20 China, 14 Indonesia, 17 Singapore, the UK 23 and the USA. 19 Where reported, the study population comprised adults and children.…”
Section: Resultsmentioning
confidence: 99%
“… 17 19 Several studies were also included that analyzed the impact of a controlled environment on screening accuracy. 21 , 57 59 For literature evaluating the efficiency of IRT screening for the detection of febrile international travelers, seventeen studies were identified: one aimed at detecting SARS in Canada; 60 four studies for Dengue detection in Taiwan; 12 , 13 , 61 , 62 five for Influenza in New Zealand, 63 , 64 Japan, 65 , 66 and Australia; 67 and three for Ebola virus disease (EVD) in the USA, Australia, and the UK, 68 and Sierra Leone; 69 , 70 one for MERS in Indonesia; 71 and three for COVID-19 in multiple countries. 72 74 For literature evaluating the detection of infectious diseases with measurements of vital signs, three studies were identified containing the required information for inclusion: two utilizing CMOS camera that was equipped with IRT; 75 , 76 two utilizing Doppler blood-flow meter, 10-GHz microwave radar, and thermography; 77 , 78 and one utilizing radar, finger-tip photoreflector, and thermography.…”
Section: Methodsmentioning
confidence: 99%
“…MERS-CoV has never been reported in Indonesia, although thousands of pilgrims have visited the Middle East every year. Despite extensive efforts to screen for MERS-CoV in 28 197 returning pilgrims in Indonesia in 2015, the study did not identify any positive cases (Amin et al, 2018).…”
Section: Introductionmentioning
confidence: 80%